(untitled) (Bulletin KNOB, 1998)
Although no less than 78 Medieval manuscripts of Vitruvius’s De Architectura Libri X (25 B.C.) have been preserved, very little is known of the needs felt in copying the text. Contemporary comments are scarce and generally do not show much more than a philological curiosity, the ars architecturae in itself being held in a rather ambivalent esteem, either as a ’free’ or ’liberal’ discipline, or, perhaps more often, as a modest, ’mechanical’ one. In addition, and in a Vitruvian tradition, we have some typical Early Medieval ’recipes’ for constructional problems, partly being copied from Late Roman sources; it is unclear whether these prescriptions were really being put into practice. On the other hand, some ten German manuals in a Late Gothic tradition present us with a coherent set of rules and guidelines for building and design. Representing the actual procedures, they may well be characterised as sound theory, reflecting at least the days from Villard to Dürer (XIII-XVI c.). Probably due to the fundamental formal differences between Classical and Medieval architecture, no attempt has as yet been made at thoroughly comparing Vitruvian design theory with the more modestly formulated ’recipes’ by the Gothic architects. In doing so, the familiarity in drawing to scale, in applying a so-called ’practical’ geometry, and in choosing design measurements becomes surprisingly obvious. So, if one cannot prove an actual influence of De Architectura because textual sources referring to it are failing, we may well knit the eyebrows at the ostentatiously declared ’rediscovery’ of Vitruvius by the Florentine humanist - and writer of farces - Poggio Bracciolini in the year 1416. The least we may assume is, that a limited but growing group of Medieval church founders, intellectuals and architects were left with enough insight - and practice - in their own days to be able to grasp not all of Vitruvius’ technical vocabulary, but certainly the foremost principles of building he once cared so much to offer us in writing.